Синяя молния: повести и рассказы / С. Т. Романовский - Романовский Станислав Тимофеевич (Золотая библиотека, 1989)
4-6кл Экземпляры: Д.О. (20210203) / Инвентарный номер: 25237 / Авт.знак: Р 69 / ГРНТИ: 17.82 / ББК: 84(2Рос)